The potential application of cellulose acetate membrane for CO2 adsorbent - Hastuti, Novitri (Environmental technology, 2024)
Numerous countries have deployed significant efforts to reduce the amount of CO2 released into the atmosphere. Carbon capture and storage is widely regarded as a mitigation technique that can significantly reduce CO2 emissions. A crucial stage in carbon capture and storage is CO2 adsorption using a membrane. Cellulose acetate has demonstrated excellent properties as a membrane material. In this study, we examined the potential of cellulose acetate membrane (CAM) for CO2 gas capture. Two forms of CAM were developed for this study, with and without the addition of glycerol. Scanning Electron Microscope (SEM), Fourier Transform Infrared (FTIR), and CO2 adsorption analyses were used to characterise CAM in numerous ways. The analysis revealed that the addition of glycerol improved the gas adsorption properties of the material. The incorporation of glycerol into the cellulose acetate matrix resulted in an observed augmentation in both the diameter and pore size. The adsorption properties of CO2 are significantly influenced by the microscopic structure of the cellulose acetate membrane. The CAM can be viewed as a possible material for CO2 adsorbers